PENGARUH METODE ROLE PLAY TERHADAP SELF ESTEEM ANAK USIA 5-6 TAHUN DI TK SWASTA KRISTEN KALAM KUDUS 2 MEDAN - Tessalonika Br L Tobing; Wan Nova Listia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Young children are those who are given the freedom to express their feelings without pressure. This study aims to determine the effect of the role-play method on the self-esteem of 5- to 6-year-old children at Kalam Kudus 2 Private Christian Kindergarten in Medan. This study is based on the phenomenon that many children are still unable to openly express their feelings, are afraid to express themselves, and tend to prioritize their friends’ feelings over their own. The method used is a quantitative approach with a Nonequivalent Control Group Design.The study population includes all 21 students in Group B. The sampling technique used is purposive sampling. The sample in this study consisted of 10 children. The instrument used to collect data was an observation sheet measuring self-esteem indicators, including feelings of acceptance, competence, and worthiness. Data analysis was conducted using the non-parametric Wilcoxon Signed Rank Test. The results of the study indicate an effect on the children’s self-esteem inthe experimental class after receiving the role-play method treatment. The mean pretest score for the experimental class changed from 19.3 to 24.3 on the posttest, with a difference of 5 points. The results of the hypothesis test showed a significance value of 0.0004, which is smaller than 0.05 (p < 0.05), meaning the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. Based on these results, it can be concluded that the role-play method has a positive effect on the self-esteem of children aged 5–6 years because it provides them with the opportunity to express their feelings, use their imagination freely, and experience social acceptance through role-playing.